Предмет:
МатематикаАвтор:
аноним1) y^2 + 6y + 9 = (y + 3)^2;
2)x^2 - 2x - 8 = 0
D = 4 - 4*(-8) = 36;
x1 = (2 - 6)/2 = -2;
x2 = (2 + 6)/2 = 4;
x^2 - 2x - 8 = (x - 4)(x + 2);
3)3x^2 - 7x + 4 = 0
D = 49 - 4*3*4 = 1;
x1 = (7 - 1)/2*3 = 1;
x2 = (7 + 1)/2*3 = 4/3;
3x^2 - 7x + 4 = 3(x - 1)(x - 4/3) = (x - 1)(3x - 4);
4) -x^2 + 3x + 10 = 0;
D = 9 - 4*(-1)*10 = 49;
x1 = (-3 - 7)/2*(-1) = 5;
x2 = (-3 + 7)/2*(-1) = -2;
3x + 10 - x^2 = -(x - 5)(x + 2) = (5 - x)(x + 2);
5)-4x^2 + 7x = x(-4x + 7) = x(7 - 4x);
6)9a^2 - 25 = (3a - 5)(3a + 5).
Автор:
schultzДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть